2020
DOI: 10.3389/fmed.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Anti-emetic Drugs for Prophylaxis of Postoperative Nausea and Vomiting After Craniotomy: An Updated Systematic Review and Network Meta-Analysis

Abstract: Background: There is uncertainty about the effect of antiemetic drugs (AED) for the prophylaxis of postoperative nausea and vomiting (PONV) after craniotomy. In this study, we assessed the effectiveness and safety of AED for PONV. Methods and Findings: We searched online databases including the Cochrane Library, PubMed, Wiley, Elsevier Science Direct, Ovid LWW, and Springer for publications from 1985 to June 2018. Adults undergoing craniotomy with the prophylactic use of at least one AED were included. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…PONV in cesarean section deliveries is still common due to the adverse effects of conventional antiemetics. [10][11][12] Figure 2: Systolic blood pressure (mmHg) Recent advances in 5-HT3 receptor antagonists such as granisetron and ondansetron have been shown to have no side effects and are popular with surgical teams. 13 However, their relative efficacy in different clinical situations is less well documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PONV in cesarean section deliveries is still common due to the adverse effects of conventional antiemetics. [10][11][12] Figure 2: Systolic blood pressure (mmHg) Recent advances in 5-HT3 receptor antagonists such as granisetron and ondansetron have been shown to have no side effects and are popular with surgical teams. 13 However, their relative efficacy in different clinical situations is less well documented.…”
Section: Discussionmentioning
confidence: 99%
“…Antiemetic prophylaxis is now the recognized method for reducing PONV. 9,10 Preventive antiemetic medication is not only beneficial but can also help patients at higher risk of PONV avoid hospitalization and additional care costs. 11 Traditional antiemetics, although tried, have their own drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…These problems mainly involve postoperative nausea and vomiting (PONV), Soon and Yoon found that 27.1% of patients experienced PONV [8]. PONV is the most common postoperative complication, with an incidence rate as high as 50% after surgery [9].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated fosaprepitant to be the most effective single agent for the prevention of craniotomy related PONV. 4 Craniotomy is known to be a risk factor for PONV, which can cause potentially catastrophic complications including surgical site bleeding, raised intracranial pressure, seizures, and death. 5 On the basis of the ubiquitous nature of the NK-1 receptor in the central and peripheral nervous system motor and sensory pathways, we sought to determine whether intraoperative fosaprepitant administration would interfere with electroencephalogram [EEG], somatosensory evoked potential [SSEP], or transcranial motor evoked potential [TcMEP] monitoring in patients undergoing general anesthesia.…”
mentioning
confidence: 99%
“…Fosaprepitant is superior to both ondansetron 2 and droperidol 3 in preventing postoperative nausea and vomiting [PONV] after craniotomy in adult patients. A recent meta-analysis demonstrated fosaprepitant to be the most effective single agent for the prevention of craniotomy related PONV 4 . Craniotomy is known to be a risk factor for PONV, which can cause potentially catastrophic complications including surgical site bleeding, raised intracranial pressure, seizures, and death 5 …”
mentioning
confidence: 99%